Induction of hepatic fibrosis in mice with schistosomiasis by extracellular microRNA-30 derived from Schistosoma japonicum eggs - Chen, Yang; Hu, Yuan; Zhou, Hao; Jiang, Nan; Wang, Yiluo; Zhang, Jing; Shen, Yujuan; Yu, Guoying; Cao, Jianping (Frontiers in Immunology, 2024)
Background Schistosomiasis is a zoonotic parasitic disorder induced by the infestation of schistosomes, a genus of trematodes. MicroRNAs (miRNAs) in egg-derived exosomes are crucial for modulating the host’s immune responses and orchestrating the pathophysiological mechanisms. Although the exosomes secreted by S. japonicum contain abundant miRNAs, the specific roles of these miRNAs in the pathogenesis of schistosomiasis-induced hepatic fibrosis are yet to be comprehensively elucidated. The egg exosomes of S. japonicum secrete miRNA-30, a novel miRNA. Methods In vitro, the effect of miRNA-30 was evaluated by transfecting HSCs with miRNA mimics. The target gene biosignature for miRNA-30 was predicted using the miRDB software. The effect of miRNA-30 in hepatic fibrosis was evaluated by either elevating its expression in healthy mice or by inhibiting its activity in infected mice by administration of recombinant adeno-associated virus serotype eight vectors expressing miRNA-30 or miRNA sponges. Results This novel miRNA can activate hepatic stellate cells (HSCs), the prinary effector cells of hepatic fibrosis, in vitro, i.e., it significantly increases the fibrogenic factors Col1(α1), Col3(α1), and α-SMA at both mRNA and protein levels. In addition, miRNA-30 may activate HSCs by targeting the host RORA gene. In addition, in vivo experiments were conducted by administering a recombinant adeno-associated viral vector to modulate the expression levels of miRNA-30. The overexpression of miRNA-30 in healthy mice significantly elevated the expression of Col1(α1), Col3(α1), and α-SMA at both the transcriptomic and proteomic scales. This overexpression was coupled with a pronounced augmentation in the hepatic hydroxyproline content. Conversely, the in vivo silencing of miRNA-30 in infected mice induced a considerable reduction in the size of hepatic granulomas and areas of collagen deposition. Hence, in vivo, modulation of miRNA-30 expression may play a pivotal role in ameliorating the severity of hepatic fibrosis in mice afflicted with S. japonica. Conclusions The study results suggest that miRNA-30 may augment schistosomiasis-induced hepatic fibrosis through a probable interaction with the host RORA. Our study may improve the current theoretical framework regarding cross-species regulation by miRNAs of hepatic fibrosis in schistosomiasis.